VD_FINDINFO Jug / 2012 / 135 vom 23. Mai 2012 - VD Tribunal cantonal (2012)
DIVORCE, PRÉVOYANCE PROFESSIONNELLE, PARTAGESENS GÉNÉRAL, INTÉRÊT MORATOIRE, INTÉRÊT RÉMUNÉRATOIRE | 122 CC, 22 LFLP, 15 al. 2 LPP, 7 OLP, 12 OPP2